IMPACT OF BACTERIAL INFECTIONS IN PERITONEAL DIALYSIS PATIENTS - NAJUMUSAQIB , M; ZAINAB, .; ULLAH , H; SALMAN , A; SABEREEN , M; BANARAS , F (Biological and Clinical Sciences Research Journal, 2023)
Bacterial infections can cause significant clinical complications in patients undergoing Peritoneal Dialysis (PD). This study aimed to determine bacterial infection’s clinical and psychosocial outcomes in PD patients. A prospective observational study enrolled 150 PD patients through non-probability sequential sampling. Demographic information, duration of PD, previous infections, and laboratory results were collected. Bacterial infections were identified through routine cultures of PD fluids, and antibiotic susceptibility was determined using the disc diffusion method. The average age of PD patients was 52.3 years, with 42% men and 58% women (p<0.05). Staphylococcus aureus infected 22 patients (14.67%), whereas Streptococci infected 18 patients (12%) (p<0.05). Antibiotic susceptibility assays determined that Staphylococcus aureus was 77% sensitive to vancomycin. Seventy-five patients (50%) on PD for more than 19 months encountered infections. Among the infected group, 90 patients (60%) recovered without complications, while 5 (4.2%) died. The study revealed a significant correlation between bacterial infections in PD patients and clinical symptoms, antibiotic resistance patterns, and disease duration. These findings highlight the importance of enhanced patient monitoring and evolving treatment strategies to improve patient outcomes.